Effects of Perceived Mathematics Connection on Mathematics Motivation: Mediating Role of History of Mathematics Concepts - Gyasi Alfred, Bannor; Yarhands Dissou, Arthur; Benjamin Adu, Obeng (International Journal of Mathematics and Mathematics Education (IJMME), 2024)
The present study assessed the mediating effects of history of mathematics concepts on the relationship between mathematics connection and mathematics motivation. The study was a descriptive survey carried out on 390 students randomly selected from Asuoso Senior High School in the Offinso-North District of Ghana’s Ashanti region. Data was collected using Likert type structured questionnaires. Reliability analysis was computed in SPSS (V. 23) and confirmatory factor analysis was computed in AMOS (V. 23). In addition, average variance extracted (AVE), convergent validity, and discriminant validity were computed in Microsoft Excel from factor loadings. Also, composite reliability was calculated at https://www.thestatisticalmind.com/composite-reliability/. Structural Equation Modelling (SEM) was computed in Amos (V. 23) to determine direct, and mediating effects among the main constructs. The study found that mathematics connection positively and significantly influenced mathematics motivation of senior high school students. The indirect effects of mathematics connection on mathematics motivation through history of mathematics concepts was positive and significant. The study recommended that mathematics teachers should desist from merely topic explanations and rote memorization of solution procedures. They should rather make mathematics connections and history of mathematics concepts imminent in their lesson planning and delivery. To implement this, mathematics topics should be linked to real-life scenarios, other subjects, and students’ lives, and the history behind such concepts are explained in plain language. Not only teachers, NaCCA should ensure that the mathematics syllabus and textbooks for senior high schools have incorporated real-life scenarios as well as the historical background of concepts to ensure learners develop the interest and motives for studying mathematics.